The Hippo Pathway in Innate Anti-microbial Immunity and Anti-tumor Immunity - Zhang, Qian; Zhou, Ruyuan; Xu, Pinglong (Frontiers in Immunology, 2020)
The Hippo pathway responds to diverse extracellular cues and plays a key role in cell fate determination, tissue homeostasis and organ regeneration. Aberrant Hippo signaling, on the other hand, has been frequently implicated in diversified pathologies such as cancer and immune dysfunctions. Here we summarized recent but rapid advances of the Hippo pathway involving in function and physiology of innate immunity, including its impacts on innate immune signaling, anti-microbial immunity, and anti-tumor immunity, with a particular focus on their inherent mechanisms and mutual interactions with innate immune signaling. Moving forward, we believe that systematic and context-dependent investigations under physiological settings are needed to draw us a clearer picture of Hippo actions in innate immunity.